Currency recognition and converter system - Nurlaila, Haman (2008)
The ease with we recognize a face, understand spoken words, read handwritten characters, identify our car keys in our pocket by feel, and decide whether an apple is ripe by it smells belies the astoundingly complex processes that underlie these acts of pattern recognition. As for currency recognition and converter system is an image processing technology that is used to identify currency amount and converts it into the other currencies as the users need. The purpose of currency recognition and converters is accurately to recognize the currencies and convert the currency immediately into the other currency. It can helps human in order to live a better life. The system based on the computer communicates with web cam, catches video frames which include a visible image of currency amount and processes them. Various methodologies are used on the surface of the image. The selected area of the image is processed and analyzed with their parameters. Once the image of the currency amount was detected, its digit is recognized it will display on the user interfaced. This program will be developed using MATLAB. MATLAB is a high – performance language for technical computing.